Antipartisanship and political tolerance in Brazil - Fuks, Mario; Ribeiro, Ednaldo; Borba, Julian (Revista de Sociologia e Política, 2021)
ABSTRACT Introduction: This article propose to connect two research agendas on political behavior: studies on political tolerance and research on partisanship. Search, by connecting these two agendas, to assess the extent to which parties have become targets of political intolerance and thereby to assess the intensity of negative attitudes towards this central institution of democracy. Studies on partisanship conflicts in Brazil have focused on the antagonism opposing petismo and antipetismo. However, the 2018 elections have shown that Brazilians also adopt other forms of antipartisanship. Changes in patterns of political and electoral behavior in recent years can only be properly understood if we consider variation over time in the intensity and scope of antipartisan sentiment. We propose a typology where antipartisanship may be moderate or radical and may have a narrower or broader target. This theme is significant not only for interpreting Brazil’s current political context, but also for deepening understanding of theoretical and analytical questions. Our understanding is that these different types of antipartisanship are distinct phenomena with different effects. Materials and Methods: The data we use to construct the proposed typology and analyze the range and intensity of antipartisanship are derived from an unprecedented Latin America Public Opinion Project initiative to measure political tolerance in Brazil, in its 2017 edition. Our methodology combine variables of disaffection and political intolerance to construct different voter profiles, based on respondent’s attitudes towards unpopular groups, including political parties. After constructing the typology, we propose regression models to estimate the effects of each type on several attitudes, like support to democracy and institutional trust. Results: Our findings show a relationship between the most extreme types of antipartisanship and attitudes towards democracy. Compared with non-antipartisan voters, intolerant antipartisan are less supportive of democracy and democratic institutions and less favorable to freedom of expression and the granting of political rights to minorities. The intensity of antipartisanship matters more than its scope, since the models show that, there is little difference in the degree of commitment to democracy and democratic principles between the two types of intolerant antipartisans, regardless of the scope of the target of their disapproval. This means that attitudes toward democracy, democratic institutions, and democratic principles depend less on the scope antipartisanship, than on political intolerance towards these groups. Discussion: The data and results presented here indicate that antipartisanship is not a one-dimensional phenomenon. The individual is not merely antipartisan or non-antipartisan. We show that antipartisanship contains at least two dimensions: its scope and intensity. Previous studies have already shown the existence of different expressions of antipartisanship, but this diversity has not yet been systematically explored using a well-defined typology. Our work points to this research agenda. KEYWORDS: antipartisanship; political tolerance; political attitudes; political parties; democracy.